2020
DOI: 10.3340/jkns.2019.0178
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Lacosamide in Experimental Peripheral Nerve Injury in Rats : A Prospective Randomized and Placebo-Controlled Trial

Abstract: Objective : To evaluate the neuroprotective effects of lacosamide after experimental peripheral nerve injury in rats. Methods : A total of 28 male wistar albino rats weighing 300-350 g were divided into four groups. In group I, the sciatic nerve exposed and the surgical wound was closed without injury; in group II, peripheral nerve injuries (PNI) was performed after dissection of the nerve; in group III, PNI was performed after dissection and lacosamide was administered, and in group IV, PNI was performed afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This same effect can be observed in experimentally induced transient cerebral ischemia, in which the possible neuroprotective effect of LCM on CA1 pyramidal neurons is due to the increase of CAT and GPX expression after pretreatment with LCM [43]. In two other studies, Demiroz et al [44,45] also demonstrated a neuroprotective effect of LCM after experimental peripheral nerve injury (PNI) and traumatic spinal cord injury (SCI). In both, the neuroprotective effect of LCM is linked to its ability to reduce the production of reactive oxygen species by increasing antioxidant enzyme expressions.…”
Section: Discussionmentioning
confidence: 59%
“…This same effect can be observed in experimentally induced transient cerebral ischemia, in which the possible neuroprotective effect of LCM on CA1 pyramidal neurons is due to the increase of CAT and GPX expression after pretreatment with LCM [43]. In two other studies, Demiroz et al [44,45] also demonstrated a neuroprotective effect of LCM after experimental peripheral nerve injury (PNI) and traumatic spinal cord injury (SCI). In both, the neuroprotective effect of LCM is linked to its ability to reduce the production of reactive oxygen species by increasing antioxidant enzyme expressions.…”
Section: Discussionmentioning
confidence: 59%